Anti-cracking machine-made sand concrete and preparation method thereof

Through the preparation of modified machine sand and the combination of basalt fibers, the problem of the machine sand concrete prone to cracks in the yellow plains is solved, the crack resistance and construction performance are improved, and the compressive strength and durability are achieved.

CN119263727APending Publication Date: 2025-01-07SHANDONG LUQIAO CONSTR

Patent Information

Application Number
CN202411334126.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the Yellow Plain area, the machine-sand concrete is prone to cracks after hardening due to the scarcity of natural sand resources, which affects the construction quality. Its surface roughness and poor particle shape lead to poor concrete pumping properties and construction performance.

Method used

By using the preparation method of modified machine sand, by adding molten glue liquid and coupling modified nanoalumina to the rotatable cylinder and irradiating ultraviolet light, it forms a smooth and regular modified machine sand, combining basalt fibers and Fly ash forms a uniform and stable concrete structure.

Benefits of technology

The crack resistance and construction performance of machined sand concrete is improved, the moisture loss rate in the mortar pores is reduced, the overall strength and compressive strength of the concrete are enhanced, and the pumping and durability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057798520000031
    Figure BDA0005057798520000031
  • Figure BDA0005057798520000041
    Figure BDA0005057798520000041
  • Figure BDA0005057798520000061
    Figure BDA0005057798520000061
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and discloses anti-cracking machine-made sand concrete and a preparation method thereof. The anti-cracking machine-made sand concrete is prepared from the following raw materials: cement, coal ash, machine-made sand, coarse aggregate, basalt fiber, water and a polycarboxylic acid water reducing agent, the modified machine-made sand is prepared by wrapping the machine-made sand with a molten rubber mixture glue solution and adhering and coupling the modified nano aluminum oxide on the outer surface of the machine-made sand. The preparation method of the anti-cracking machine-made sand concrete comprises the following steps: mixing dry materials to prepare a mixture, adding water and a water reducing agent into the mixture to prepare mortar, and adding coarse aggregate into the mortar to prepare the machine-made sand concrete. The modified machine-made sand is smooth in surface, regular in shape and easy to uniformly disperse in concrete mortar, the loss speed of free water in mortar pores is reduced, and the anti-cracking performance of machine-made sand concrete can be improved after the modified machine-made sand is doped into the concrete mortar.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a crack-resistant machine-made sand concrete and a preparation method thereof. Background Art

[0002] The Yellow River flood plain in Shandong is mainly concentrated in the west and northwest of Shandong. There are few exploitable natural sand resources. Especially in the construction of highways in some mountainous areas or deserts, there are more stones than sand, and natural sand resources are very scarce. It is imperative to replace natural sand with machine-made sand to prepare concrete. The properties of machine-made sand (particle grading, particle shape, surface roughness, etc.) have a great influence on the water demand of silicate cement concrete mixture. Different water consumption leads to great differences in shrinkage, cracks and durability of concrete after hardening. Due to the rough surface, sharp edges and poor particle shape of machine-made sand, the mixed machine-made sand concrete has a high water demand, is easy to segregate, and has poor pumpability. Especially when preparing low-grade machine-made sand concrete, the amount of cementitious materials is small, the concrete is discrete, has poor cohesion, poor water retention, poor fluidity, and the pumpability and construction performance cannot be guaranteed. In addition, the Yellow River Flood Plain has strong and frequent winds, little precipitation, dry air, rapid warming, strong solar radiation, and large water evaporation. This climate feature easily leads to plastic shrinkage and drying shrinkage of concrete, which in turn forms plastic cracks and shrinkage cracks in concrete. In particular, concrete made with machine-made sand loses water faster and is more prone to cracks, seriously affecting the construction quality of concrete structures. Therefore, how to make the characteristics of machine-made sand closer to or even better than natural river sand, while making the preparation method simple and easy, is a technical problem that needs to be solved urgently. Summary of the invention

[0003] In order to solve the above technical problems, a machine-made sand concrete is developed. The present application provides a crack-resistant machine-made sand concrete and a preparation method thereof.

[0004] In a first aspect, the present application provides a machine-made sand concrete, comprising the following raw materials in parts by weight: 300-400 parts of cement, 80-130 parts of fly ash, 500-750 parts of machine-made sand, 800-1100 parts of coarse aggregate, 18-32 parts of basalt fiber, 120-180 parts of water, and 11-16 parts of polycarboxylic acid water reducer; the machine-made sand includes modified machine-made sand.

[0005] Furthermore, the preparation method of the modified machine-made sand includes the following steps: placing the machine-made sand in a rotatable cylinder, adding 5-12wt% of molten glue while rotating the cylinder, rotating the cylinder for 2-3h, adding 1.5-3wt% of coupled modified nano-alumina, rotating the cylinder for 0.2-0.5h to obtain a modified masterbatch, and irradiating the modified masterbatch with an ultraviolet light source to obtain modified machine-made sand.

[0006] Furthermore, the linear speed of the rotatable cylinder during rotation is 2-4 m / s.

[0007] Furthermore, the irradiation dose of the ultraviolet light source is 10-20 Mard.

[0008] Furthermore, the preparation method of the coupled modified nano-alumina includes the following steps: adding silane coupling agent KH-550 to anhydrous ethanol, stirring for 2 minutes, then adding nano-alumina, ultrasonicating for 10 minutes, filtering out the residue, and drying to obtain coupled modified nano-alumina; wherein the weight ratio of the silane coupling agent, anhydrous ethanol and nano-alumina is 0.5-0.8:9-15:1.

[0009] By adopting the above technical scheme, the present application uses the rubber glue after mixing to wrap the machine-made sand to form a rubber layer, and adheres a trace amount of coupled modified nano-alumina on the surface of the rubber layer before the rubber layer is completely vulcanized, and then controls the irradiation dose of ultraviolet radiation to make it vulcanized, thereby improving the corrosion resistance and water resistance of the rubber layer; the molten rubber can effectively fill the holes of the machine-made sand, and the machine-made sand rotates in the cylinder, collides and rubs against each other, while the molten rubber continuously fills the pores on the surface of the machine-made sand, so that the surface of the machine-made sand after vulcanization is smoother and the shape is more regular, thereby promoting the dispersion of the modified machine-made sand in the cement mortar, which is beneficial to reducing the generation of large pores in the mortar, and can greatly reduce the loss rate of free water in the pores of the mortar, thereby improving the crack resistance of the machine-made sand concrete; the nano-alumina on the surface of the modified machine-made sand can be combined with the aluminum silicate gel in the mortar, and has a higher specific surface area and adsorption performance, and the adsorbed metal cations are concentrated around the gel, which is beneficial to promote the uniform distribution of the modified machine-made sand in the mortar.

[0010] Furthermore, the method for preparing the molten adhesive comprises the following steps: adding acrylic rubber, SBS rubber particles, tackifying resin, antioxidant, crosslinking agent and vulcanizing agent into an internal mixer for internal mixing to obtain the molten adhesive.

[0011] Furthermore, in the preparation process of the molten rubber, the weight ratio of the acrylic rubber, the SBS rubber particles, the tackifying resin, the antioxidant, the crosslinking agent and the vulcanizing agent is 70-90:40-50:14-20:0.4-0.6:2-3.5:0.5-0.8.

[0012] Furthermore, the machine-made sand includes 14-27 wt % of modified machine-made sand.

[0013] Furthermore, the fineness modulus of the machine-made sand is 2.3-3.0.

[0014] Furthermore, the coarse aggregate includes large stones and small stones, the particle size of the large stones is 8-28 mm, the particle size of the small stones is 3.5-7.9 mm, and the weight ratio of the large stones to the small stones is 5-8:3-5.

[0015] Furthermore, the length of the basalt fiber is 5-25 mm.

[0016] The length of basalt is selected to be 5-25mm. At this length, basalt fiber and coarse aggregate are compounded to support each other to form a reinforcement structure for the whole concrete. Artificial sand and fly ash are filled under this structure, which is conducive to forming a uniform, stable internal structure with strong mechanical properties, thereby enhancing the overall strength and crack resistance of the artificial sand concrete.

[0017] In a second aspect, the present application provides a method for preparing the above-mentioned anti-cracking machine-made sand concrete, comprising the following steps: S1. Mix cement, fly ash and machine-made sand and stir for 10-20 minutes to obtain a mixture; S2, adding 60-75% of the total amount of water to the mixture prepared in step S1, stirring for 5-10 minutes, then adding polycarboxylate water reducer and the remaining amount of water while stirring, stirring for 5-10 minutes, to prepare machine-made sand mortar; S3. Add coarse aggregate to the machine-made sand mortar prepared in step S2 while stirring, and stir for 10-20 minutes to prepare crack-resistant machine-made sand concrete.

[0018] In summary, the present invention includes at least one of the following beneficial technical effects: 1. In this application, modified machine-made sand is used to make machine-made sand concrete. The machine-made sand prepared in this application has a smooth surface and a regular shape, is easy to disperse evenly in the concrete mortar, reduces the loss rate of free water in the pores of the mortar, and improves the crack resistance of the machine-made sand concrete.

[0019] 2. The method for preparing machine-made sand concrete in this application is simple and easy, the cost of raw materials is low, the prepared concrete has high compressive strength and good crack resistance, and has good commercial value. DETAILED DESCRIPTION

[0020] The present application is further described in detail below in conjunction with specific embodiments.

[0021] The present application designs a crack-resistant machine-made sand concrete, comprising the following raw materials in parts by weight: 300-400 parts of cement, 80-130 parts of fly ash, 500-750 parts of machine-made sand, 800-1100 parts of coarse aggregate, 18-32 parts of basalt fiber, 120-180 parts of water, and 11-16 parts of polycarboxylate water reducer; the machine-made sand includes modified machine-made sand.

[0022] The preparation method of the modified machine-made sand comprises the following steps: placing the machine-made sand in a rotatable cylinder, adding 5-12wt% of molten glue while rotating the cylinder, rotating the cylinder for 2-3h, adding coupling-modified nano-alumina particles, rotating the cylinder for 0.5-1h to obtain a modified masterbatch, and irradiating the modified masterbatch with an ultraviolet light source to obtain the modified machine-made sand.

[0023] The anti-cracking machine-made sand concrete of the present application is prepared by the following method, comprising the following steps: S1. Mix cement, fly ash and machine-made sand and stir for 10-20 minutes to obtain a mixture; S2, adding 60-75% of the total amount of water to the mixture prepared in step S1, stirring for 5-10 minutes, then adding polycarboxylate water reducer and the remaining amount of water while stirring, stirring for 5-10 minutes, to prepare machine-made sand mortar; S3. Add coarse aggregate to the machine-made sand mortar prepared in step S2 while stirring, and stir for 10-20 minutes to prepare crack-resistant machine-made sand concrete.

[0024] The technical problem solved by this application is that the application of concrete made of machine-made sand in the Yellow River Flood Plain easily leads to abnormal shrinkage of concrete, thus forming plastic cracks and shrinkage cracks in concrete, which seriously affects the construction quality of concrete structures. This application adopts modified machine-made sand to make machine-made sand concrete. The obtained machine-made sand has a smooth surface and regular shape, is easy to disperse evenly in concrete mortar, reduces the loss rate of free water in the pores of mortar, and improves the crack resistance of machine-made sand concrete.

[0025] Examples 1-5 Examples 1-5 are crack-resistant machine-made sand concretes made with different raw material ratios. The specific raw material ratios are shown in Table 1 (unit: parts by weight).

[0026] Table 1 The fineness modulus of the machine-made sand used in Implementation 1-5 is between 2.3 and 3.0, corresponding to medium sand, with a particle size distribution in the range of 1.18-2.36 mm, and a stone powder mass content of about 12%.

[0027] The cement type used in Examples 1-5 is PO42.5 silicate cement.

[0028] The fly ash used in Examples 1-5 is Class II fly ash.

[0029] The weight ratio of large stones to small stones in the coarse aggregate used in Examples 1-5 is 6:4, wherein the average particle size of the large stones is 22 mm, and the average particle size of the small stones is 6 mm.

[0030] The average length of the basalt fibers used in Examples 1-5 is 20 mm.

[0031] The polycarboxylate water reducer used in Examples 1-5 is Lome LM-S2.

[0032] The machine-made sand in Examples 1-5 includes about 22 wt % of modified machine-made sand; the preparation method of the modified machine-made sand in Examples 1-5 includes the following steps: (1) placing acrylic rubber, SBS rubber particles, tackifying resin, antioxidant, crosslinking agent and vulcanizing agent in a weight ratio of 85:40:16:0.5:3:0.6 in an internal mixer at 180° C. and mixing for 20 minutes to obtain a molten rubber solution; (2) The machine-made sand is placed in a rotatable cylinder, and a molten glue accounting for about 9 wt% of the mass of the machine-made sand is sprayed into the inner wall of the cylinder while the cylinder is rotated. The cylinder is rotated for 2.5 hours, and coupled modified nano-alumina accounting for about 2 wt% of the mass of the machine-made sand is added. The cylinder is rotated for 0.3 hours to obtain a modified masterbatch. The modified masterbatch is irradiated with an ultraviolet light source, and the irradiation dose is controlled to be 16 Mard to obtain modified machine-made sand.

[0033] The tackifying resin is liquid rosin resin, the antioxidant is triphenyl phosphite, the cross-linking agent is pentaerythritol tetraacrylate, and the vulcanizing agent is N,N-di-cinnamyl-1,6-hexanediamine.

[0034] The preparation method of coupled modified nano alumina comprises the following steps: adding silane coupling agent KH-550 to anhydrous ethanol, stirring for 2 minutes, then adding nano alumina, ultrasonicating for 10 minutes, filtering to obtain the filter residue, and drying to obtain coupled modified nano alumina; wherein the weight ratio of silane coupling agent, anhydrous ethanol and nano alumina is 0.6:12:1.

[0035] The method for preparing the crack-resistant machine-made sand concrete in Examples 1-5 comprises the following steps: S1. Mix cement, fly ash and machine-made sand and stir for 12 minutes to obtain a mixture; S2, adding 70% of the total amount of water to the mixture prepared in step S1, stirring for 8 minutes, then adding polycarboxylate water reducer and the remaining amount of water while stirring, stirring for 6 minutes, to prepare machine-made sand mortar; S3. Add coarse aggregate to the machine-made sand mortar prepared in step S2 while stirring, and stir for 15 minutes to prepare crack-resistant machine-made sand concrete.

[0036] Example 6 Example 6 is based on Example 2, except that the method for preparing modified machine-made sand in Example 6 comprises the following steps: (1) placing acrylic rubber, SBS rubber particles, tackifying resin, antioxidant, crosslinking agent and vulcanizing agent in a weight ratio of 85:40:16:0.5:3:0.6 in an internal mixer at 180° C. and mixing for 20 minutes to obtain a molten rubber solution; (2) The machine-made sand is placed in a rotatable cylinder, and a molten glue accounting for about 9 wt% of the mass of the machine-made sand is sprayed from the inner wall of the cylinder while the cylinder is rotated. The cylinder is rotated for 2.5 h and 0.3 h to obtain a modified masterbatch. The modified masterbatch is irradiated with an ultraviolet light source, and the irradiation dose is controlled to be 16 Mard to obtain modified machine-made sand.

[0037] Embodiment 7-8 Example 7 is based on Example 2, with the difference that the machine-made sand in Example 7 includes modified machine-made sand accounting for 14 wt% of the total machine-made sand.

[0038] Example 8 is based on Example 2, with the difference that the machine-made sand in Example 8 includes modified machine-made sand accounting for 27 wt% of the total machine-made sand.

[0039] Example 9 Example 9 is based on Example 2, with the difference that the average particle size of the large stones in the coarse aggregate in Example 9 is 12 mm.

[0040] Example 10 Example 10 is based on Example 2, except that the average length of the basalt fibers in Example 10 is 12 mm.

[0041] Examples 11-12 Example 11 is based on Example 2, with the difference that the fineness modulus of the machine-made sand used in Example 11 is 3.1-3.7, corresponding to coarse sand, and the average particle size is about 5 mm.

[0042] Example 12 is based on Example 2, with the difference that the fineness modulus of the machine-made sand used in Example 12 is 1.6-2.2, corresponding to fine sand, and the average particle size is about 0.8 mm.

[0043] Comparative Example 1 Comparative Example 1 is based on Example 2, with the difference that the machine-made sand in Comparative Example 1 does not include modified machine-made sand.

[0044] Performance Testing 1. With reference to the slump test method in standard GB / T50080-2002 "Standard Industry Standard and National Specification for Test Methods for Performance of Ordinary Concrete Mixtures", practical slump tests were performed on Examples 1-12 of the present application and Comparative Example 1. The test results are shown in Table 2.

[0045] 2. Referring to the compressive strength test method in standard G8 / T50081-2016 "Yingtong Concrete Mechanical Properties Test Method Standard", 7d and 28d compressive strength tests were performed on Examples 1-12 and Comparative Example 1. The measurement results are shown in Table 2.

[0046] 3. According to the standard G / T50081-2016 "Test Method for Mechanical Properties of Ordinary Concrete", 6 test blocks were prepared for each embodiment or comparative example, and the number of cracks per unit area obtained after 24 hours of concrete pouring (cracks / mm 2 ), the test results are taken as the average value of 6 test blocks, and the test results are shown in Table 2.

[0047] 4. The test was carried out in accordance with the standard GB / T50082-2009 "Test method for long-term performance and durability of ordinary concrete". The specifications of the molded test blocks were standard truncated cones of 175mm×185mm×150mm. Six test blocks were grouped together and the standard curing was 28 days. The test pieces were taken out of the curing room one day before reaching the corresponding age. After the surface of the test pieces was dried, they were sealed and then the water seepage height test was carried out to measure the water seepage height (mm). The test results were taken as the average value of the six test blocks. The test results are shown in Table 2.

[0048] Table 2 By analyzing the data in Table 2, it can be obtained by comparing Examples 1-5 with Comparative Example 1 that the use of rubber material wrapped on the machine-made sand can reduce the drying shrinkage of concrete and prevent concrete cracking. After being added to concrete, it can effectively improve the impermeability and crack resistance of concrete; the water seepage height of Comparative Example 1, which does not use modified machine-made sand, is significantly increased, and the surface cracks increase while the impermeability decreases, indicating that the addition of modified machine-made sand can improve the carbonization resistance and impermeability of concrete, and improve the roundness of machine-made sand, thereby improving the slump of concrete. In addition, by comparing Example 2 with Example 6, it can be obtained that coating a layer of nano-alumina on the surface of the modified concrete is conducive to promoting the uniform distribution of the modified machine-made sand in the concrete mortar, thereby further improving the impermeability and crack resistance of the concrete.

[0049] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A crack-resistant machine-made sand concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 300-400 parts of cement, 80-130 parts of fly ash, 500-750 parts of machine-made sand, 800-1100 parts of coarse aggregate, 18-32 parts of basalt fiber, 120-180 parts of water, 11-16 parts of polycarboxylate water reducer; The machine-made sand includes modified machine-made sand.

2. The anti-cracking machine-made sand concrete according to claim 1, characterized in that: The preparation method of the modified machine-made sand comprises the following steps: placing the machine-made sand in a rotatable cylinder, adding 5-12wt% of molten glue while rotating the cylinder, rotating the cylinder for 2-3h, adding 1.5-3wt% of coupled modified nano-alumina, rotating the cylinder for 0.2-0.5h to obtain a modified masterbatch, and irradiating the modified masterbatch with an ultraviolet light source to obtain the modified machine-made sand.

3. The anti-cracking machine-made sand concrete according to claim 2, characterized in that: The preparation method of the molten adhesive comprises the following steps: adding acrylate rubber, SBS rubber particles, tackifying resin, antioxidant, crosslinking agent and vulcanizing agent into an internal mixer for melting to obtain the molten adhesive.

4. The anti-cracking machine-made sand concrete according to claim 2, characterized in that: In the preparation process of the molten glue, the weight ratio of the acrylic rubber, the SBS rubber particles, the tackifying resin, the antioxidant, the crosslinking agent and the vulcanizing agent is 70-90:40-50:14-20:0.4-0.6:2-3.5:0.5-0.

8.

5. The anti-cracking machine-made sand concrete according to claim 1, characterized in that: The machine-made sand comprises 14-27wt% of modified machine-made sand.

6. The anti-cracking machine-made sand concrete according to claim 1, characterized in that: The fineness modulus of the machine-made sand is 2.3-3.

0.

7. The anti-cracking machine-made sand concrete according to claim 1, characterized in that: The coarse aggregate includes large stones and small stones. The particle size of the large stones is 8-28 mm, the particle size of the small stones is 3.5-7.9 mm, and the weight ratio of the large stones to the small stones is 5-8:3-5.

8. The anti-cracking machine-made sand concrete according to claim 1, characterized in that: The length of the basalt fiber is 5-25 mm.

9. A method for preparing crack-resistant machine-made sand concrete according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Mix cement, fly ash and machine-made sand and stir for 10-20 minutes to obtain a mixture; S2. Add 60-75% of the total amount of water to the mixture prepared in step S1, stir for 5-10 minutes, then add polycarboxylate water reducer and the remaining amount of water while stirring, and stir for 5-10 minutes to prepare machine-made sand mortar; S3. Add coarse aggregate to the machine-made sand mortar prepared in step S2 while stirring, and stir for 10-20 minutes to prepare crack-resistant machine-made sand concrete.

Citation Information

Patent Citations

  • C30 high-impermeability concrete with low cementing material consumption and preparation method thereof

    CN111704409A

Cited By

  • Industrial solid waste-based flexible composite material as well as preparation method and application thereof

    CN119551945A